An enhanced approach to simulation-based mastery learning: optimising the educational impact of a novel, National Postgraduate Medical Boot Camp - Emma L. Scahill; Nathan G. Oliver; Victoria R. Tallentire; Simon Edgar; James F. Tiernan (Advances in Simulation, 2021)
Abstract Background Simulation-based mastery learning (SBML) is an effective, evidence-based methodology for procedural skill acquisition, but its application may be limited by its resource intensive nature. To address this issue, an enhanced SBML programme has been developed by the addition of both pre-learning and peer learning components. These components allowed the enhanced programme to be scaled up and delivered to 106 postgraduate doctors participating in a national educational teaching programme. Methods The pre-learning component consisted of an online reading pack and videos. The peer learning component consisted of peer-assisted deliberate practice and peer observation of assessment and feedback within the SBML session. Anonymised pre- and post-course questionnaires were completed by learners who participated in the enhanced programme. A mixture of quantitative and qualitative data was obtained. Results Questionnaires were distributed to and completed by 50 learners. Both sections of the pre-learning component were highly rated on the basis of a seven-point Likert scale. The peer learning component was also favourably received following a Likert scale rating. Peer observation of the performance and assessment process was rated similarly by first and second learners. The thematic analysis of the reasons for which peer-assisted deliberate practice was considered useful showed that familiarisation with equipment, the rehearsal of the procedure itself, the exchange of experiences and sharing of useful tips were important. The thematic analysis of the reasons why peer observation during ‘performance, assessment and feedback’ was useful highlighted that an ability to compare a peer’s performance to their own and learning from observing a peer’s mistakes were particularly helpful. Conclusion The SBML programme described has been enhanced by the addition of pre-learning and peer learning components which are educationally valued and allow its application on a national scale.